PENGOLAHAN MINYAK KEMIRI DENGAN CARA PELARUTAN DAN PENGEMPAAN - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The objective of this research is to study the processing of candle nut oils by using solvent extraction and pressing techniques. In a solvent extraction technique, several solvents were applied in the experiment. The choice solvent was used to extract the treated candle nut seeds. In a pressing technique, five levels of pressing temperature were applied to extract untreated candle nut seeds. The effect of the temperatures was calculated by a complete randomized design. Relationship between the pressing temperature and oil properties was analysed with a polynomial orthogonal method.Results showed that a hexane solvent with pure analytical grade was the best solvent to extract candle nut oils as indicated by the highest yield of oils. Using this solvent, a dry-frying treatment on candle nut seeds gave the highest yield of oils, compared boiling and control treatments. In a pressing technique, the increasing of pressing temperature gave a highly significant effect on yields, specific gravity, peroxide and iodine numbers. It also gave a significant effecr on saponifiable number. A polynomial orthogonal analysis showed that pressing temperatures had a highly significant quadratic relationship to oil yields or iodine number, a linear relationship to peroxide number or spesific gravity, and a significant cubic relationship to saponification number. Based on the regression equation for iodine number, the optimum value of iodine number was obtained at a 93° C pressing temperature. At this temperature, the oil yield which could be produced was 59, 79 %. The candle ma oil produced at this temperature was the best oil quality, as indicated by the highest value of iodine number, 97.28.